DNA Commission of the International Society for Forensic Genetics: Recommendations on the validation of software programs performing biostatistical calculations for forensic genetics applications. (November 2016) - Coble, M.D.; Buckleton, J.; Butler, J.M.; Egeland, T.; Fimmers, R.; Gill, P.; Gusmão, L.; Guttman, B.; Krawczak, M.; Morling, N.; Parson, W.; Pinto, N.; et al.
Highlights: The International Society for Forensic Genetics (ISFG) has convened a DNA Commission to establish validation guidelines for bio-statistical software to be used in forensic genetics. We present recommendations for the minimum requirements to validate bio-statistical software for forensic genetics. Recommendations are provided for developmental validation and the responsibilities of the software developer. Recommendations for internal validation and the responsibilities of the end user are also provided. Abstract: The use of biostatistical software programs to assist in data interpretation and calculate likelihood ratios is essential to forensic geneticists and part of the daily case work flow for both kinship and DNA identification laboratories. Previous recommendations issued by the DNA Commission of the International Society for Forensic Genetics (ISFG) covered the application of bio-statistical evaluations for STR typing results in identification and kinship cases, and this is now being expanded to provide best practices regarding validation and verification of the software required for these calculations. With larger multiplexes, more complex mixtures, and increasing requests for extended family testing, laboratories are relying more than ever on specific software solutions and sufficient validation, training and extensive documentation are of upmost importance. Here, we present recommendations for the minimum requirements to validate bio-statistical software to be used in forensic genetics. We distinguish between developmental validation and the responsibilities of the software developer or provider, and the internal validation studies to be performed by the end user. Recommendations for the software provider address, for example, the documentation of the underlying models used by the software, validation data expectations, version control, implementation and training support, as well as continuity and user notifications. For the internal validations the recommendations include: creating a validation plan, requirements for the range of samples to be tested, Standard Operating Procedure development, and internal laboratory training and education. To ensure that all laboratories have access to a wide range of samples for validation and training purposes the ISFG DNA commission encourages collaborative studies and public repositories of STR typing results.